2016
DOI: 10.1017/s1751731116000239
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pure Holsteins to crossbred Holsteins with Norwegian Red cattle in first and second generations

Abstract: A total of 1922 first generation crossbred cows born between 2005 and 2012 produced by inseminating purebred Israeli Holstein cows with Norwegian Red semen, and 7487 purebred Israeli Holstein cows of the same age in the same 50 herds were analyzed for production, calving traits, fertility, calving diseases, body condition score, abortion rate and survival under intensive commercial management conditions. Holstein cows were higher than crossbreds for 305-day milk, fat and protein production. Differences were 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
5
6
4
Order By: Relevance
“…The milk produced by crossbred cows was richer in protein and casein compared with the milk from purebred Ho cows, confirming results reported by Heins and Hansen (2012), Ezra et al (2016), andHazel et al (2017b), who looked at 2-breed crosses using Mo or Nordic Red sires on Ho cows, and by Malchiodi et al (2014b) and Shonka- Martin et al (2019a), who examined 3-breed crosses of the Ho, Mo, and VR breeds.…”
Section: Comparison Between Purebred Ho and Crossbred Cowssupporting
confidence: 81%
“…The milk produced by crossbred cows was richer in protein and casein compared with the milk from purebred Ho cows, confirming results reported by Heins and Hansen (2012), Ezra et al (2016), andHazel et al (2017b), who looked at 2-breed crosses using Mo or Nordic Red sires on Ho cows, and by Malchiodi et al (2014b) and Shonka- Martin et al (2019a), who examined 3-breed crosses of the Ho, Mo, and VR breeds.…”
Section: Comparison Between Purebred Ho and Crossbred Cowssupporting
confidence: 81%
“…An opposite conclusion was drawn from the study by Blöttner and others () who recorded no significant differences in SCC between HF and HF×BS cows. Ezra and others () also found no differences in SCC between HF and HF×NRF cows. In addition, Heins and Hansen () concluded that SCC in HF×NO crosses was similar to SCC in HF cows, and that it was significantly lower in the crosses of HF×MO and HF with bulls of the Scandinavian breeds.…”
Section: Resultsmentioning
confidence: 83%
“…This was also confirmed by Swalve and others () and Van Raden and Sanders (). However, Ezra and others () showed no significant differences in the fat content of milk from HF and HF×NRF cows.…”
Section: Resultsmentioning
confidence: 83%
“…Similar results were found in full lactation, approximately 400 kg (371.89; As for fat plus protein (kg) in 305 days the same authors mentioned that crossbreeds had 3 to 10 % lower values comparing to HF. Opposite results were obtained by Ezra et al (2016), who state that Holsteins were higher for milk, fat and protein production comparing to crossbreeds in F1 generations. Ezra et al (2016) also confirmed a slightly higher concentration (%) for fat and protein of the F1 crosses comparing to pure Holstein, which agrees with the results of this research.…”
Section: Resultsmentioning
confidence: 79%
“…When used properly, heterosis can be a bonus on top of the gain from traditional dairy cattle breeding programs. On contrary, Ezra et al (2016) stated that crossbreeding is a common strategy for most agricultural animal species, including poultry, swine, sheep and beef cattle but for dairy cattle crossbreeding has generally not been considered as an economically viable option. According to Buckley et al (2014) the economic improvement using crossbreeding can be achieved by introducing favourable genes from another breed selected more strongly for traits of interest; removing the negative effects associated with inbreeding depression; or by benefits of heterosis effect.…”
Section: Introductionmentioning
confidence: 99%